(untitled) (GEON Journal (Management, Organizations and Business), 2015)
The world is changing at a rapid pace driven by the impact of information technology and communication (ICT), globalization and internationalization, which have impacted the dynamics of society. These changes have not been oblivious to how to proceed from the companies and governments in many countries, given that as trade barriers that divide the world are reduced, companies feel the need to change the profiles of executives and workers who want to have in their institutions, which is why we must develop new professional skills related to the understanding of the values of multiculturalism. Looking for that purpose, the Higher Education Institutions (IES) have developed strategies for regional, national and international mobility as a way to create space for students to develop the ability to function in an efficient manner in various multicultural environments. This research identified among students of a private higher education institutions in the city of Santiago de Cali, motivations to participate in the program and the perception of its operation, identifying the main motivation is related to improving their coping skills and acculturation and its formation as a person and professional. Generally positive perception about the processes and action clearly directed towards better.